تفعيل نشاط فهم المنطوق بالصورة التعليمية في السنة أولى متوسط (Revue El-Wahat pour les Recherches et les Etudes, 2023)
ملخص: يعتبر نشاط فهم المنطوق من الأنشطة التعليمية المقرّرة في المدرسة الجزائرية، الذي يتوسّم من برمجته رفع كفاءة المتعلم في التحصيل المعرفي والاكتساب اللغوي، ويُكتفَى في إنجازه  بتفعيل مهارة سماع الأستاذ وهو يقرأ النص دون أن يطّلع عليه المتعلم أو أن يكون له سابق معرفة بمحتواه، وهذا ما يميّزه عن الأنشطة التربوية الأخرى، وتقترح الورقة البحثية هذه مرافقة الصورة لهذا النشاط في السنة أولى من التعليم المتوسط بالجزائر آلية إجرائية لبلوغ الهدف المنشود من برمجة هذا النشاط؛ نشاطا تربويا قائما بذاته، لإبراز ما للصورة التعليمية من أهمية في تفعيل هذا النشاط التربوي الهادف، وخاصة إذا تقاطعت في الدلالة مع محتوى النص المقرّر، فتتكامل معه ليبلغا معا المعرفة المستهدفة.كلمات دالة: فهم المنطوق؛ السماع؛ الصورة التعليمية؛ النص التعليمي؛ الاكتساب اللغوي.    Abstract :            The spoken Understanding task is one of the important educational tasks designed for Algerian middle school learners. The task aims at developing the learner’s linguistic competence as well as mastery of content. In this task, the learner is expected to listen to the teacher reading the text aloud. What distinguishes the task from other tasks is that the learner does not need to have prior knowledge about it. Thus, the present study examines the use of the didactic picture in the task of understanding the spoken for first year Algerian middle school learners. Besides, the study highlights the role of the didactic picture in strengthening this purposeful activity; they accomplished each other to achieve together the target knowledge. Key words: the spoken understanding; listening; the didactic picture; the didactic text; language acquisition.